2012
DOI: 10.1002/ppap.201200047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Damage of Glutathione by Glow Discharge Plasma at the Gas–Solution Interface through Raman Spectroscopy

Abstract: Although non‐thermal discharge plasma is more and more applied in biological field, the molecular mechanisms of plasma acting on biomolecules are still unclear, which are indispensable for understanding the plasma‐induced biological effects. In this work, discharge plasma at the gas–solution interface was employed to irradiate on reduced glutathione (GSH), the most abundant low molecular weight thiol‐containing antioxidant in cells. Through Raman spectroscopy, both the irreversible damage and reversible conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Therefore, we have checked the quantitative analysis in Table 2 , where we can observe the change in amino acids after treatment with plasma. The change in the weight of amino acids after treatment is due to oxidation, nitration, dehydrogenation and dimerization as suggested by literature 37 38 39 40 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we have checked the quantitative analysis in Table 2 , where we can observe the change in amino acids after treatment with plasma. The change in the weight of amino acids after treatment is due to oxidation, nitration, dehydrogenation and dimerization as suggested by literature 37 38 39 40 .…”
Section: Discussionmentioning
confidence: 84%
“…It was observed that OH radical dependent abstraction of a hydrogen atom from the α-carbon of amino acids, aliphatic side chains of hydrophobic amino acid residues of protein and from the protein polypeptide backbone seem to be the possible initial sites of attack 31 32 36 . There are some studies of the plasma action on amino acids by different research groups 37 38 39 40 . They observed the disulfide linkage formation and hydroxylation of amino acids after the plasma treatment.…”
mentioning
confidence: 99%
“…It was reported that this type of plasma sources was applied so far to the purification of water from organic dyes [8][9][10][11], phenol [12][13][14], or organic halides [15][16][17] and to the sterilization of water [1,18] and its bio-decontamination [19][20][21]. The discoloration of wastewaters containing various dyes and the decomposition of other organic compounds by glow discharges (GDs) were rather frequently studied in various plasma reactors and electrode configurations, i.e., discharges in liquids termed as glow discharge electrolysis (GDE) [10,16], discharges in contact with liquids termed as contact glow discharge electrolysis (CGDE) [6,9,12,[20][21][22][23] and discharges between two liquids separated by thin diaphragm holes termed as diaphragm glow discharge (DGD) [11,17]. It was also possible to inactivate glutathione [20], cyanotoxins (microcystin-LR) [21] or cyanobacteria (microcystis aeruginosa) in fresh waters by CGDEs [22].…”
Section: Introductionmentioning
confidence: 99%
“…The discoloration of wastewaters containing various dyes and the decomposition of other organic compounds by glow discharges (GDs) were rather frequently studied in various plasma reactors and electrode configurations, i.e., discharges in liquids termed as glow discharge electrolysis (GDE) [10,16], discharges in contact with liquids termed as contact glow discharge electrolysis (CGDE) [6,9,12,[20][21][22][23] and discharges between two liquids separated by thin diaphragm holes termed as diaphragm glow discharge (DGD) [11,17]. It was also possible to inactivate glutathione [20], cyanotoxins (microcystin-LR) [21] or cyanobacteria (microcystis aeruginosa) in fresh waters by CGDEs [22]. The removal of inorganic hazardous chemicals from waters by APGDs was faintly examined.…”
Section: Introductionmentioning
confidence: 99%
“…Because proteins and amino acids strongly influence biological reactions, an understanding of chemical reactions of amino acids under a discharge plasma is important for determining the mechanism of the biological effects of the discharge plasma. Discharge plasma reportedly induces chemical modifications of peptides and amino acids such as phenylalanine [17], methionine [18], and glutathione [19]. However, little is known about the reactions of amino acids with low molecular weight under a discharge plasma.…”
Section: Introductionmentioning
confidence: 99%